Functional Bacterial Cellulose-Based MXene (Ti3C2Tx) Electronic-Skin Patch for Accelerated Healing and Monitoring - Saliha Nur lIhan; Bahar Akyuz Yilmaz; Fatih Ciftci (BME Frontiers)
Objective: This study aims to develop and characterize electroactive hydrogels based on reduced bacterial cellulose (BC) and Ti3C2Tx-MXene for their potential application in wound healing and real-time monitoring. Impact Statement: The integration of Ti3C2Tx-MXene into BC matrices represents a novel approach to creating multifunctional hydrogels that combine biocompatibility, electrical conductivity, and mechanical durability. These properties make the hydrogels promising candidates for advanced wound care and real-time monitoring applications. Introduction: Wound healing requires materials that support cell growth, promote tissue regeneration, and enable real-time monitoring. MXenes, a class of 2-dimensional materials, offer unique electrical and mechanical properties, making them suitable for biomedical applications. This study explores the integration of Ti3C2Tx-MXene with BC, a biopolymer known for its excellent biocompatibility and mechanical strength, to create electroactive composite hydrogel films for advanced wound care. Methods: Ti3C2Tx-MXene was synthesized by etching Ti3AlC2 with hydrofluoric acid and integrated into BC pellicles produced by Gluconacetobacter xylinum. The composite hydrogel films underwent characterization through x-ray diffraction (XRD), x-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR), and thermogravimetric analysis (TGA) to determine structural, chemical, and thermal properties. Mechanical testing assessed tensile and compressive strengths. Biological assessments, including cell viability, hemolysis rate, and protein expression, evaluated biocompatibility and regenerative potential. Results: XRD confirmed the crystallographic structure of MXene and BC composite film. XPS and FTIR validated the successful incorporation of MXene into the film matrix. Composite hydrogel films demonstrated a tensile strength of 3.5 MPa and a compressive strength of 4.2 MPa. TGA showed stability up to 350 °C, and the electrical conductivity reached 9.14 × 10−4 S/m, enabling real-time monitoring capabilities. Cell viability exceeded 95%, with a hemolysis rate below 2%. Protein expression studies revealed the ability to promote skin regeneration through collagen I, K10, K5, and filaggrin expression. Conclusion: The BC/MXene composite hydrogel films exhibit important potential as electronic-skin patches for accelerating wound healing and enabling real-time monitoring. Their unique combination of mechanical durability, electrical conductivity, and biocompatibility highlights their promise for advanced wound care applications.